Association between quality of life and resilience in infertile patients: a systematic review - Liu, Kexian; Dou, Shanshan; Qin, Wei; Zhao, Di; Zheng, Wei; Wang, Dan; Zhang, Caixia; Guan, Yichun; Tian, Peiling (Frontiers in Public Health, 2024)
This systematic review was carried out to describe QoL and resilience in infertile patients, as well as the relationship between them, and to give a theoretical foundation for clinical practice. The databases of CNKI, Wanfang data, VIP database, PubMed, Web of Science, and Embase were searched without a time limit. A narrative synthesis of relevant articles was undertaken. This systematic review was registered on PROSPERO in advance. Of 21 studies eligible for inclusion in this review, 13 focused on the relationship between QoL and resilience, 5 on QoL influencing factors (resilience included), and 3 on mediation effect analysis on mental health (resilience as a mediator). Resilience can significantly predict the QoL of infertile patients. It seems plausible that more resilient couples will be less vulnerable to the stress of infertility. A global consortium of infertile population research could make cross-cultural comparisons of QoL and resilience possible. Future research should focus on resilience therapies. Systematic review registration This systematic review was registered on PROSPERO in advance (CRD42023414706).